Survivors [compact disc, unabridged] : a novel of the coming collapse - Rawles, James Wesley (Brilliance Audio, 2011)
The America we are accustomed to is no more. Practically overnight the stock market has plummeted, hyperinflation has crippled commerce, and the fragile chains of supply and high-technology infrastructure have fallen. The power grids are down. Brutal rioting and looting grip every major city. In this unfamiliar environment, only a handful of individuals are equipped to survive.